2019
DOI: 10.3390/diagnostics9040147
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Workup in Patients with Meibomian Gland Dysfunction Treated with Intense Regulated Pulsed Light

Abstract: The purpose of the present study was to evaluate changes of signs and symptoms in patients with meibomian gland dysfunction (MGD) treated with intense regulated pulsed light (IRPL), and to further investigate which parameter could predict positive outcomes of the procedure. Twenty-eight patients who bilaterally received three IRPL sessions at day 1, 15, and 45 satisfied the criteria and were included in the study. Non-invasive break-up time (NIBUT), lipid layer thickness (LLT), meibography, tear osmolarity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“… 22 Additionally, LLL is the only treatment that was applied directly to the upper lid ( Table 1 ). The improvement in lipid layer thickness was frequently described in IPL without LLL treatment, 8 , 13 , 15 , 17 , 18 , 23 but other studies are showing no effect. 19 , 24 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 22 Additionally, LLL is the only treatment that was applied directly to the upper lid ( Table 1 ). The improvement in lipid layer thickness was frequently described in IPL without LLL treatment, 8 , 13 , 15 , 17 , 18 , 23 but other studies are showing no effect. 19 , 24 …”
Section: Discussionmentioning
confidence: 91%
“…This can be explained by the higher increment on the lipid layer (solute) compared to the increment on the aqueous layer (solvent). In IPL without LLL studies, the tear osmolarity has been reported as lowered 23 , 24 or unchanged. 8 , 13 , 14 , 19 According to important studies, 25–27 it was expected that DED symptoms and OSDI score would worsen with increasing osmolarity, but this wasn´t the case.…”
Section: Discussionmentioning
confidence: 98%
“…However, no differences were found between days 75 and 45, suggesting that two sessions were enough to reduce the signs and symptoms of MGD. Vigo et al [ 74 ] (III) also performed follow-up visits on day 1, 15, and 45. They found an improvement in NIBUT, LLT, and osmolarity and suggested that patients with lower BUT responded better to the treatment.…”
Section: Light-based Devicesmentioning
confidence: 99%
“…There is a lack of agreement in the IPL treatment protocol. The number of sessions varies among three [ 74 , 76 ], four [ 73 , 77 , 78 ], and eight [ 79 ], and the period between sessions can fluctuate between 15 [ 73 , 74 , 77 ], 21 [ 78 , 79 ] and 30 [ 76 , 77 ] days. Finally, the number of flashes is not standardized, 4–5 being the most frequent [ 73 – 75 , 80 ], although other authors double the flashes or apply even more [ 78 , 79 ].…”
Section: Light-based Devicesmentioning
confidence: 99%
“…The severity of bulbar redness can be objectively quantified via an automated and standardized image grading system. Moreover, meibography and ocular surface staining are two critical assessment for identifying evaporative dry eye [ 13 , 14 ] and ocular surface disease severity of dry eye [ 15 , 16 ], respectively.…”
Section: Introductionmentioning
confidence: 99%